Glimpse of Ancient Social History through the Social Structure of The Mahabharata Period - Adhikari, Shukra Raj; Adhikari, Bhawani Shankar; Acharya, Ganga; Dahal, Samyog; Adhikari, Bijaya; Sharma, Tilak (History Department, Semarang State University and Historian Society of Indonesia, 2024)
The Mahabharata is one of the historical literature that displays the historical linkage of the sociocultural structure of contemporary society. In this context, this paper has focused on exploring the economic system, family structure, marriage patterns, slavery system, political leadership, Ashram system, and the dimensions of conflict as the social history and parts of the social structure of The Mahabharata period. It reflects a historical glimpse of an earlier epoch of 500 BC. Nowadays, observing and visiting the ancient social structure of the Mahabharata period is impossible. So, historical data was collected through the historical content analysis method as secondary sources to gain the objective. The objective-wise thematic stanzas and historical interpretations of The Mahabharata have been collected as qualitative data. Similarly, primary data was gathered using the experts’ interaction method. The content analysis method has been used to analyze this study’s primary and secondary data types. The social and cultural structure of the Mahabharata period was found to be constructed on the foundation of the historical context of slavery and the feudalistic mode of production system. The slavery and feudalistic social structure are always linked to patriarchal and patrilineage socio-cultural practices. Based on this background and roots, the social structure of The Mahabharata has been shaped, formed, and determined. These facts are congruent with the theoretical mode of production and interpretation of Marxism’s conflict-oriented perspective.Mahabharata merupakan salah satu karya sastra sejarah yang menampilkan keterkaitan sejarah dengan struktur sosiokultural masyarakat kontemporer. Dalam konteks ini, tulisan ini fokus mengeksplorasi sistem ekonomi, struktur keluarga, pola perkawinan, sistem perbudakan, kepemimpinan politik, sistem ashram, dan dimensi konflik sebagai sejarah sosial dan bagian dari struktur sosial periode Mahabharata. Ini mencerminkan sekilas sejarah dari zaman awal tahun 500 SM. Saat ini, mengamati dan mengunjungi struktur sosial kuno pada masa Mahabharata adalah hal yang mustahil. Jadi, data sejarah dikumpulkan melalui metode analisis isi sejarah sebagai sumber sekunder untuk mencapai tujuan. Bait tematik objektif dan interpretasi sejarah Mahabharata dikumpulkan sebagai data kualitatif. Demikian pula, data primer dikumpulkan dengan menggunakan metode interaksi para ahli. Metode analisis isi digunakan untuk menganalisis jenis data primer dan sekunder penelitian ini. Struktur sosial dan budaya periode Mahabharata ditemukan dibangun di atas fondasi konteks sejarah perbudakan dan cara sistem produksi feodalistik. Perbudakan dan struktur sosial yang feodalistik selalu dikaitkan dengan praktik sosial budaya yang bersifat patriarki dan patrilinease. Berdasarkan latar belakang dan akar tersebut, struktur sosial Mahabharata dibentuk, dibentuk, dan ditentukan. Fakta-fakta ini selaras dengan cara produksi teoritis dan interpretasi perspektif berorientasi konflik Marxisme.